FISCAL POLICY AND PRO POOR SPENDING IN MALAWI - Jambo, Hellen Nancy (My University, 2011)
This study carried out an analysis of the Malawi fiscal policy pro poor spending between 2004 and 2008 in relation to poverty reduction. The focus of the research was to investigate how much the three social pillars that formed the premises of this study were allocated out of the yearly budget between 2004 and 2008. Since a descriptive statistical analysis was carried out besides the process issues behind budget formulation and analysis being carried out, a mix methodology was used to investigate and address the research questions. The findings of the study show that poverty remains high in Malawi despite the increased pro poor expenditure as such there is a need for a policy intervention. Not much progress has been achieved with regards poverty reduction between 2004 and 2008. It was discovered that the same percentage of people that moved out of poverty moved back into the poverty trap. In conclusion, the study makes a couple of policy recommendations that are aimed at directing current expenditure towards programmes and initiatives that will drive poverty reduction at an accelerated rate than is at present. Some are in enforcing governance so that budget implementation is efficient and effective
MM - P&DM
Keywords: Fiscal policy, Malawi; Poverty reduction, Malawi